Pengaruh Kemandirian Belajar Matematika Peserta Didik terhadap Hasil Belajar Peserta Didik Di MAN Keerom - Surwanti Anggraeni; Abdul Rachman Taufik (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
This study aims to analyze and examine the effect of students' mathematics learning independence on the learning outcomes of MAN KEEROM students. The method used in this research is correlational method with quantitative data. The population in this study were students of MAN KEEEROM class 10 with a sample of 4 people on the wrong side. The instruments in this study were 13 questionnaires and 5 number essay tests related to matrix material. Then the results of this study concluded that the effect of learning independence (X) on Mathematics Learning Outcomes (Y) of students was 68.4% while the remaining 31.6% was influenced by other factors not examined.